Enhancing Sustainable Groundwater Governance through the Groundwater Management Information System (GMIS): A Case Study of Punjab, Pakistan - Ullah, Muhammad Kaleem; Hafeez, Mohsin; Iqbal, Naveed; Cheema, Muhammad Jehanzeb Masud; Siddiqui, Salman; Aeman, Hafsa; Zafar, Haseeb; Bodla, Habibullah; Ashraf, Muhammad (2025)
Pakistan is facing an escalating water crisis, intensified by climate change impacts over the past two decades. Limited freshwater resources and rising competition among agricultural, domestic, and industrial users have worsened water scarcity. Punjab—Pakistan’s agricultural hub—is experiencing a severe groundwater crisis, marked by rapid depletion (e.g., 6.89 ft/year in Depalpur) and contamination (e.g., arsenic >171.8 µg/L in Renala Khurd), threatening water security for 120 million people. This study assesses the transformative role of the Groundwater Management Information System (GMIS), developed under the Water Resource Accountability in Pakistan (WRAP) Programme. It examines GMIS’s institutional, technical, and policy linkages. Backed by the Punjab Water Act 2019, GMIS enables bodies like the Punjab Water Resources Commission to enforce extraction limits (e.g., 300–400 ft drilling bans) and prioritize domestic use in contamination zones. GMIS operationalizes national and provincial policies, including the National Water Policy 2018, through integrated dashboards supporting conjunctive water management and climate-resilient solutions, such as solar-powered tubewells.